Interactive Multimedia in Teaching Reading - Sari, Indah Novita (ELLITE, 2018)
This research is intended to investigate the effectiveness of interactive multimediafor teaching reading in junior high school. Based on my preliminary research,there were many problems in teaching and learning reading for junior highschool students. Seeing those problems, the researcher tried to implement theinteractive multimedia in teaching reading. Then, the method used in thisresearch is quasi experimental with test as the instrument for collecting thedata. The students’ score was analyzed using SPSS (independent sample t-test).The result revealed that the statistical value of t-test was 4.325 and the degree offreedom of 46 at significant level 5 % was 2.02. It means that the t-value (4.325)is higher than critical value 2.02 (4.325 2.02). Therefore, the students whowere taught using interactive multimedia had better achievement in readingrather than those who were not taught using interactive multimedia.